King Kong - Jackson, Peter; Watts, Naomi; Jack Black; Adrien Brody; Thomas Kretschmann; Colin Hanks; Andy Serkis; Evan Parke; Jamie Bell; Lobo Chan; John Sumner; Craig Hall; et al. (NewZealand Big Primate Pictures, 2005)
In 1933 New York, an overly ambitious movie producer coerces his cast and hired ship crew to travel to mysterious Skull Island, where they encounter Kong, a giant ape who is immediately smitten with leading lady Ann Darrow.
Set in the 1930s, this is the story of a young and beautiful actress Ann Darrow from the world of vaudeville who finds herself lost in depression-era New York and her luck changes when she meets an over-ambitious filmmaker Carl Denham who brings her on an exploratory expedition to a remote island where she finds compassion and the true meaning of humanity with an ape Kong. The beauty and the beast finally meet their fate back in the city of New York where the filmmaker takes and displays the ape in quest of his fame by commercial exploitation which ultimately leads to catastrophe for everyone including a playwright Jack Driscoll who falls in love with Ann and plays an unlikely hero by trying to save her from Kong and her destiny.
Languages: English, Czech Subtitles: English, Czech, Bulgarian, Romanian, Turkish
Keywords: Action; Adventure; Drama; Mystery; Thriller